Roll-to-Roll (R2R) High-Throughput Manufacturing of Foil-Based Microfluidic Chips for Neurite Outgrowth Studies - Nihan Atak; Martin Smolka; Anja Haase; Alexandra Lorenz; Silvia Schobesberger; Stephan Ruttloff; Christian Wolf; Ana Ayerdi-Izquierdo; Peter Ertl; Nerea Briz Iceta; Jan Hesse; Martin Frauenlob (Micromachines, 2025)
Microfluidic devices have emerged as a pivotal in vitro technology for axon outgrowth studies, facilitating the separation of the cell body from the neurites by geometric constraints. However, traditional microfabrication techniques fall short in terms of scalability for large-scale production, hindering widespread application. This study presents the development of foil-based cell culture chips, made of polyethylene terephthalate and in-house formulated ultraviolet curable liquid resin by high-throughput roll-to-roll (R2R) manufacturing. Here, two microchannel designs were tested to optimize manufacturing quality and assess the neurite outgrowth behavior. The fabricated neuron-foil chips demonstrated biocompatibility and supported neurite outgrowth within microchannels under static cell culture conditions. Furthermore, fluidic flow, oriented either perpendicular or parallel to the microchannel direction, was applied to enhance the biological reproducibility within the neuron-foil chips. These findings suggest that R2R manufacturing offers a promising approach for the high-throughput production of biocompatible microfluidic devices, advancing their potential application in modeling neurological diseases within the biomedical industry.